Improving Student Learning Outcomes in Al-Qur'an Hadith Learning through the Index Card Match Model at MIS NU Setia Mukti - Juju Julianti; Julhida (MANDAILING GLOBAL EDUKASIA, 2025)
The learning outcomes of the Al-Qur'an Hadith material